2017
DOI: 10.2147/ijn.s130861
|View full text |Cite
|
Sign up to set email alerts
|

NIR responsive liposomal system for rapid release of drugs in cancer therapy

Abstract: To design a rapid release liposomal system for cancer therapy, a NIR responsive bubble-generating thermosensitive liposome (BTSL) system combined with photothermal agent (Cypate), doxorubicin (DOX), and NH 4 HCO 3 was developed. Cypate/DOX-BTSL exhibited a good aqueous stability, photostability, and photothermal effect. In vitro release suggested that the amounts of DOX released from BTSL were obviously higher than that of (NH 4 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…These factors include the device/method of HT (since the device affects tumor temperature distribution) (19), the applied temperature, and the HT duration (11, 20, 21). Prior preclinical studies with TSL employed varying HT durations ranging from 2 to 60 min (9, 24, 12, 22, 25, 19, 26, 20), with all studies limited to a single duration except for three recent reports that examined two HT durations (11, 20, 21). In the current study we demonstrated that the amount of Dox delivered to tumors quantified by HPLC increased with HT duration, for the three durations of 15, 30 and 60 min (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include the device/method of HT (since the device affects tumor temperature distribution) (19), the applied temperature, and the HT duration (11, 20, 21). Prior preclinical studies with TSL employed varying HT durations ranging from 2 to 60 min (9, 24, 12, 22, 25, 19, 26, 20), with all studies limited to a single duration except for three recent reports that examined two HT durations (11, 20, 21). In the current study we demonstrated that the amount of Dox delivered to tumors quantified by HPLC increased with HT duration, for the three durations of 15, 30 and 60 min (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the duration of HT dictates drug uptake (20, 21). Both the duration and method of HT in preclinical animal studies differ considerably, with HT duration ranging from 2 to 12 min for RFA (12, 20), 2 to 40 min for HIFU (22, 23), 60 min for heated water bath (9, 24, 25) and cold light lamp (19), and 5 to 60 min when a laser was used as heat source (19, 26).…”
Section: Introductionmentioning
confidence: 99%
“…The wavelengths preferred in biomedical applications are in the NIR regions (∼700−1100 nm) because at this wavelength the light penetration is more than 1 cm. 72 Chen et al 95 designed a NIR responsive bubble-generating thermosensitive liposome (BTSL) system entrapping the reactive carbocyanine dye (Cypate), DOX, and NH 4 HCO 3 . Cypate is a NIR fluorescent dye with an absorbance maximum at 778 nm and an emission maximum at 805 nm with a high extinction coefficient of 224,000 (mol/L) −1 cm −1 .…”
Section: ■ Stimuli-responsive Liposomesmentioning
confidence: 99%
“…For example, laser irradiation can be used to produce fluorescence or luminescence images, and to simultaneously induce drug release [141]. Chen et al developed a near-infrared (NIR) responsive liposomal system for rapid drug release [142]. Lipid carriers containing ammonium bicarbonate and cypate dye were found to immediately generate bubbles when exposed to NIR irradiation, which enhanced lipid bilayer permeability and drug release.…”
Section: Strategies For Controlled Releasementioning
confidence: 99%